Answer:
a = 6
Step-by-step explanation:
-6(2 + a) = -48
it is basically 2 steps
Divide by -6 first
(2 + a) = -48 / -6
2 + a = 8
minus the 2
a =6
Step-by-step explanation:
sue = 18 sweets
tony= 18 sweets
(sue) S= (18 - x)-5
(tony) T=(18 + x) ÷ 2
hope this helps :)
(2 - 7z)(2 + 7z)
= (2)^2 - (7z)^2
= 4 - 49z^2
(b). → Simplify: [{5^(x-+1) + 5^x}/{6×5^x}]
= [{5^(x+1+x)}/{6×5^x}]
= [{5^(2x+1)}/{6×5^x}]
= [{5^(2x+1)}/{6×5^x}]
= [{5^(2x+1-x)}/6]
= [{5^(x+1)}/6]Ans.
(c). 4a³b²
= 4(3)³(-2)²
Since, a = 3 and b = -2.
so,
= 4(3*3*3)(-2*-2)
= 4(27)(4)
= 108(4)
= 432Ans.
<u>also</u><u> </u><u>read</u><u> similar</u><u> questions</u><u>:</u> simplify 6/x-6+3x/x+5-1/(x-6)(x+5)..
brainly.com/question/9027174?referrer
simplify the equation simplify x^5/8/x^1/6..
brainly.com/question/84093?referrer
In 1 hour she earns $7.25
18 hours she earns $130.5
18 times 17.25 it’s $130.5